Mortality, Population and Community Dynamics of the Glass Sponge Dominated Community “The Forest of the Weird” From the Ridge Seamount, Johnston Atoll, Pacific Ocean - Mitchell, Emily G.; Harris, Simon (Frontiers in Marine Science, 2020)
The ecosystem dynamics of benthic communities depend on the relative importance of organism reproductive traits, environmental factors, inter-specific interactions and mortality processes. The fine-scale community ecology of sessile organisms can be investigated using spatial analyses because the position of the specimens on the substrate (their spatial positions) reflects the biological and ecological processes that they were subject to in-life. Consequently, spatial point process analyses (SPPA) and Bayesian network inference (BNI) can be used to reveal key insights into the ecological dynamics of these deep-sea communities. Here we use these analyses to investigate the ecology of deep-sea glass sponge dominated community "The Forest of the Weird" (2442m depth, Ridge Seamount, Johnston Atoll, Pacific Ocean). A 3D reconstruction was made of this community using photogrammetry of video stills taken from high-resolution ROV video. The community was dominated by two genera of Hexactinellids: Farreidae Aspidoscopulia sp. and Euplectellidae Bolosominae sp. with octocorals Narella bowersi, Narella macrocalyx and Rhodaniridogorgia also present in large proportions. SPPA of the dead versus alive organisms revealed a random distribution of dead amongst the living, showing a non-density dependent cause of death for the majority of taxa. However, in the high-density ridge crest region there was non-random aggregation of dead specimens, revealing density-dependent mortality for Aspidoscopulia. SPPA showed that the glass sponges and octocorals were each most strongly influenced by different underlying processes, and reacted to the environmental conditions differently. The octocorals responded to higher density areas with increased intra-specific competition, whilst the glass-sponges seemed impervious to a doubling of specimen density. BNI found that mutual habitat associations between different taxa resulted in inter-specific competition at larger (2-4m) spatial scales, with instances of competition at small-spatial scales (<0.75m) in the higher-density ridge crest section. To our knowledge, this study is the first to analyze the mortality, population and community dynamics of a deep-sea sponge community using spatial point process analyses. Our results provide the first insight into the variety of ecological behaviors of these different glass sponges and octocorals, and show how these different organisms have developed diverse responses to the biological and environmental gradients within their habitat.